2017
DOI: 10.5539/ijbm.v12n12p204
|View full text |Cite
|
Sign up to set email alerts
|

Using Balanced Scorecard for Managing Performance in Selected Ghanaian Banks

Abstract: Prior to 1992, Kaplan and Norton posited that organizations solely rely on financial measures to manage their performance. It has become possible for organizations to incorporate in addition to financial measures nonfinancial measures to manage their performance. It is in this light that balanced scorecard is one of the tools used to manage performance. However, managing the overall performance of organizations using balanced scorecard is limited in literature in Ghanaian banks. This study explores the extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…From the performance measurement results, the IPB management department has achieved a performance achievement of 80%. (Agyeman et al, 2017)…”
Section: Engineering Science Inventionmentioning
confidence: 99%
“…From the performance measurement results, the IPB management department has achieved a performance achievement of 80%. (Agyeman et al, 2017)…”
Section: Engineering Science Inventionmentioning
confidence: 99%
“…male and female of both bank branches who are working in different departments (sales and marketing, finance, remittances, clearing) are selected for the study. The questionnaire survey was adopted and modified from Agyeman et al, 2017& Murith, 2015,that is divided into four sections as discussed below: The first section of the questionnaire consist of demographic information i.e. consist of age, academic background and departments.…”
Section: Methodsmentioning
confidence: 99%
“…Quality Agyeman et al (2017) revealed that the most used BSC perspectives are: The financial perspective, customer perspective, learning and growth perspective, and internal business process respectively. Furthermore, Babar (2016) revealed that there is a positive relationship between bank's performance and using learning and growth perspective.…”
Section: F Effect Of Learning and Growth Perspective On Earningsmentioning
confidence: 99%
“…Whereas, Bassiouny (2016) confirmed that there is insignificant correlation between firm size and earnings quality. According to Agyeman et al (2017) and Turegun (2016), there is direct and significant correlation between firm size and earnings management as large scale firms tend to exercise earnings management as these firms are under great pressure in order to achieve the financial analysts' expectations.…”
Section: H Firm Sizementioning
confidence: 99%